Biocontrol of Fruit Discoloring and Fruit Rot Disease in Longan (Dimocarpus longan) by Using Antagonistic Bacillus spp. - Suksakol, Sakkarin; Liamkraituan, Jirapinya; Teeraarunsiri, Weerachai; Na Chiangmai, Pantipa; Mahadtanapuk, Supuk (Trends in Sciences, 2024)
Fruit discoloration and fruit rot disease in longan is a serious disease caused by the pathogenic fungi Pestalotiopsis oxyanthi and Lasiodiplodia pseudotheobromae. This study investigated the potential of antagonistic bacteria as an eco-friendly alternative to traditional fungicides for managing longan diseases caused by these fungal pathogens. Two bacterial isolates, UP-JLS050 and UP-JLS067, demonstrated significant inhibitory activity against the pathogenic fungi P. oxyanthi and L. pseudotheobromae, with high inhibitory activity. The bacterial strains were isolated from leaves and soil in a longan garden, and dual culture methods showed that the isolates UP-JLS050 and UP-JLS067 exhibited the highest inhibitory activity on the fungal pathogens, with percentage inhibitions of 72.67 ± 2.31 and 70.37 ± 1.28 %, respectively. Biochemical methods and molecular techniques, including sequencing of the 16S rDNA gene, were then used to identify the isolates. This confirmed their similarity to Bacillus subtilis and Bacillus amyloliquefaciens with 100 and 99 % identity, respectively. In vitro tests on longan fruit indicated that these antagonistic bacteria, administered at a concentration of 108 CFU/mL, significantly reduced disease incidence by up to 45 % after 9 days of incubation. The incubation of B. subtilis (UP-JLS050) and B. amyloliquefaciens (UP-JLS050) reduced disease incidence by 45 ± 5.77 and 32.5 ± 5.00 %, respectively. HIGHLIGHTS Fruit Discoloration and Rot in Longan: Caused by pathogenic fungi, namely Pestalotiopsis oxyanthi and Lasiodiplodia pseudotheobromae Antagonistic Bacteria for Disease Control: This study explores the potential of antagonistic bacteria as an eco-friendly alternative to traditional fungicides for managing longan diseases caused by these fungal pathogens Effective Inhibition: Two bacterial isolates, UP-JLS050 and UP-JLS067, demonstrated significant inhibitory activity against oxyanthi and L. pseudotheobromae, with inhibitions exceeding 70 % on PDA medium Identification of Bacterial Strains: Molecular techniques, including 16S rDNA gene sequencing, confirmed the identity of these isolates as subtilis and B. amyloliquefaciens Reduced Disease Incidence: In vitro tests on longan fruit indicated that these antagonistic bacteria, administered at a concentration of 108 CFU/ml, significantly reduced disease incidence by up to 45 % after 9 days of incubation GRAPHICAL ABSTRACT